Current methods of measuring the parameters of green plants - Бовсуновський, Є.О.; Рябчевський, О.В.; Браткова, К.Ю. (Science-based technologies, 2018)
Green plantations on the territory of Ukraine do not have properly issued passports, which leads to the impossibility of recording, operating and forecasting their development. To create a passport of green plantations, including trees, it is necessary to define parameters such as the area of ​​the territory where the objects under investigation are located, as well as the main parameters of the trees: type, age, height, crown diameter, positioning in GPS coordinates.The need to modernize the process of measuring metric parameters consists in reducing labor costs through the introduction of modern methods and the use of more sophisticated electronic equipment, which reduces the use of manual labor and increases overall productivity Described the current methods of measuring tree parameters. Has been conducted an analysis of the use of software products for Android-based devices: ON Distance, Smart Tools, «Высотомер», Smart Measure, ON 2D Measure to determine the diameter, height and distance to trees. The most accurate software product is installed by the value of the smallest average error - ON Distance.